2002
DOI: 10.1002/ijc.10542
|View full text |Cite
|
Sign up to set email alerts
|

PTEN expression is associated with prognosis for patients with advanced endometrial carcinoma undergoing postoperative chemotherapy

Abstract: The prognostic significance of PTEN expression in endometrial carcinoma has not been clear. We conducted the present study to clarify the relationship between PTEN expression and prognosis in advanced endometrial carcinoma. 4 showed that PTEN ϩ/-mice over 6 months old frequently developed endometrial carcinoma. These findings suggest that PTEN is strongly involved in the development and/or progression of endometrial carcinoma.Studies have also shown the relationship between PTEN and prognosis in several cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 9 publications
5
30
1
Order By: Relevance
“…The clinical implication of loss of PTEN protein expression in extrahepatic cholangiocarcinoma has not been previously investigated. Several studies showed that loss of PTEN protein expression could be used as a prognostic factor in other malignancies, including breast (34), endometrial (35), hepatocellular (36), and gastric carcinomas (37). In this study, we showed that loss of PTEN expression was associated with worse survival outcome in patients with extrahepatic cholangiocarcinoma by univariate analyses.…”
Section: Discussionsupporting
confidence: 56%
“…The clinical implication of loss of PTEN protein expression in extrahepatic cholangiocarcinoma has not been previously investigated. Several studies showed that loss of PTEN protein expression could be used as a prognostic factor in other malignancies, including breast (34), endometrial (35), hepatocellular (36), and gastric carcinomas (37). In this study, we showed that loss of PTEN expression was associated with worse survival outcome in patients with extrahepatic cholangiocarcinoma by univariate analyses.…”
Section: Discussionsupporting
confidence: 56%
“…Among them, partial genes have been previously reported to be associated with EC prognosis, such as TP53 23, 24, PIK3CA 25, CDKN2A 26, 27, and PTEN 17. By performing KEGG enrichment analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the lipid phosphatase of PTEN decreases intracellular PIP3 level and downstream Akt activity (19). Hundreds of PTEN mutations or inactivation have been found in a variety of human tumors, including brain, bladder, breast, prostate, and endometrial cancers (23)(24)(25)(26), making PTEN the second most frequently mutated tumor suppressor gene (21). Recently, PTEN has also been shown to be a critical tumor suppressor in melanoma tumorigenesis (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%